The Effect of Changes in Macroeconomic Conditions on Indonesian Sharia Stock Return - Wahyudi, Heru; Awaluddin, Imam; Murwiati, Asih; Nirmala, Tiara; Leny, Sandra Mei; Rohman, Fatkhur (International Journal of Economics and Financial Issues, 2025)
The Islamic stock market in Indonesia experiences significant fluctuations due to the dynamics of global and domestic macroeconomic conditions. Instability in interest rates, Gross Domestic Product growth, inflation, and exchange rates are the main factors that affect Islamic stock returns, as measured by the Indonesia Islamic Stock Index (ISSI). The urgency of this research is based on the importance of a more comprehensive understanding of the relationship between macroeconomic variables and Islamic stock performance, along with the development of the Islamic financial industry and increasing global economic uncertainty. This study aims to analyse the effect of macroeconomic variables on Islamic stock returns, with the hypothesis that interest rates and inflation have a negative effect, while GDP and exchange rates have a positive effect on Islamic stock returns. The research method used is Robust Least Square covering the period 2015-2023. The results showed that interest rates (−0.0157) and inflation (−0.0656) have a significant negative effect on Islamic stock returns, while GDP (0.0164) and exchange rates (1.5022) have a significant positive effect. The coefficient of determination (R-squared) of 60.14% indicates that this model is able to explain most of the variation in Islamic stock returns due to changes in macroeconomic conditions. The implications of this research include recommendations for regulators, investors, and policy makers in designing strategies that are more adaptive to macroeconomic changes. Interest rate stabilisation and inflation control policies need to be optimised to maintain the attractiveness of the Islamic capital market. In addition, strengthening Islamic financial regulations and diversifying Islamic-based investments are strategic steps to increase market resilience to global economic volatility.